1993
DOI: 10.1021/bi00071a017
|View full text |Cite
|
Sign up to set email alerts
|

Exchange, efflux and substrate binding by cysteine mutants of the lactose permease of Escherichia coli

Abstract: Citation for published version (APA): Iwaarden, P. R. V., Driessen, A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 34 publications
6
46
0
Order By: Relevance
“…Mutation C154G results in a phenotype that binds ligand but does little or no translocation of lactose across the membrane (42,43,44), and the protein appears to be locked in an outwardly facing conformation (44). When this mutation is combined with the A122C/C148A mutations, LacY binds ligand with about 10 times greater affinity than mutant A122C/ C148A but catalyzes essentially no lactose translocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation C154G results in a phenotype that binds ligand but does little or no translocation of lactose across the membrane (42,43,44), and the protein appears to be locked in an outwardly facing conformation (44). When this mutation is combined with the A122C/C148A mutations, LacY binds ligand with about 10 times greater affinity than mutant A122C/ C148A but catalyzes essentially no lactose translocation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the marked increase in the rate of reaction in the presence of ⌬ H ϩ suggests more interesting possibilities. To investigate the problem further, the A122C/C148A mutations were combined with C154G, a mutation that leads to increased binding affinity but almost complete loss of transport activity (42,43,44). RSO vesicles with mutant A122C/C148A/C154G exhibit a K d of about 20 M, about 10-fold lower than mutant A122C/C148A, as determined by TDG protection against alkylation with NEM (Table I).…”
Section: Inactivation By Mts-galactoside Occurs At Amentioning
confidence: 99%
“…Interestingly, the LacY(C148S) mutant displays monophasic (non-equilibrium exchange) kinetics with only the high affinity state for lactose, whereas the wild-type protein exhibits biphasic kinetics with both a high and low icapp [279]. The maximal rates of efflux ~tx M and exchange of the C148S mutant are about 5-fold reduced relative to the wild-type LacY protein, and high affinity binding of NPG is no longer detected in LacY(C148S).…”
Section: Vii-c Cysteine Residuesmentioning
confidence: 97%
“…Specifically, it has been suggested that in LacY sulfhydryl-disulfide interchange occurs either as intermediate of the respiratory chain [272] or as proton carrier that is affected by Ap-mediated redox changes [273,274]. However, characterization of LacY mutated at each of the 8 cysteinyl residues in the molecule has demonstrated that none of the cysteines is essential for transport [275]. Even the cysteine-less LacY protein displays significant lactose-H + symport activity [276].…”
Section: Vii-c Cysteine Residuesmentioning
confidence: 99%
See 1 more Smart Citation